A review of microbial corrosion in reclaimed water pipelines: challenges and mitigation strategies. Issue 3 (27th January 2022) - Yang, Guangming; Gong, Min; Zheng, Xingwen; Lin, Li; Fan, Jinlong; Liu, Feng; Meng, Junchen
Abstract: With the continuous development and expansion of the water reclamation and reuse market, it is vital to ensure water quality safety and stability over the entire water reuse system. Because the quality of reclaimed water is distinct from that of drinking water, it is likely to deteriorate, even after advanced treatment, during distribution and transport. This review identifies the common microbial corrosion in reclaimed water distribution pipelines and end use applications (e.g. industrial cooling system) and the dominant corrosive microorganisms in reclaimed water. The microbial corrosion mechanism and the affecting factors on microbial corrosion are discussed in depth. Moreover, this study also proposes possible strategies for dealing with pipeline microbial corrosion, including the control of the assimilable organic carbon content via coagulation and filtration processes as well as disinfection technologies for microbial inactivation. This study is of great novelty to provide a comprehensive overview of microbial corrosion in reclaimed water distribution and application and point out future directions towards sustainable and long-lasting water reuse. HIGHLIGHTS: Reclaimed water technology; Microbial corrosion; Pipeline materials; Control strategies